Genome-wide association study and haplotype analyses reveal the genetic architecture of agronomic traits and sugars in sweet sorghum - Abdullah Bin Umar; Ajay Prasanth Ramalingam; Bushra Sadia; Faisal Saeed Awan; Farooq Ahmad Khan; Mariam Nasir; Amy Bernardo; Paul St. Amand; Guihua Bai; P. V. Vara Prasad; Ramasamy Perumal (Frontiers in Genetics)
IntroductionSweet sorghum is a C4 tropical grass species that has gained importance quickly as a major bioenergy crop.MethodsThis genome-wide association study (GWAS) utilized a sweet sorghum panel (SSP) of 183 diverse sweet sorghum accessions genotyped by 14,819 high-quality single-nucleotide polymorphism (SNP) markers to identify novel genetic loci that are associated with major agronomic traits and sugars (Brix units, %).ResultsPopulation stratification revealed a clear separation of the accessions based on geographical origins. The initial 50% linkage disequilibrium (LD) decay was approximately 5 kb, and the background level was approximately 80 kb, similar to that of the previously reported sorghum association panel (SAP), indicating the panel's effectiveness and reliability for GWAS. This study identified 21 significant quantitative trait nucleotides (QTNs) for the studied traits using the three (compressed)-variance component multi-locus random- SNP-effect mixed linear model (3VmrMLM), which were colocalized with previously reported quantitative trait loci (QTLs). The phenotypic variance (R2) explained by these QTNs ranged from 5.11% to 13.86%.DiscussionAdditionally, haplotype analysis revealed significant phenotypic differences between haplotypes for four candidate genes, namely, Sobic.006G128200 (a threonine-specific protein kinase gene) for days to flowering, Sobic.001G387600 (an ethylene-insensitive gene) for Brix, Sobic.003G069950 (a protein kinase domain gene), and Sobic.003G214400 (an amino acid transporter gene) for fresh biomass.